The Italian foreign constituency and its MPs. Issue 2 (4th May 2017) - Sampugnaro, Rossana
ABSTRACT: More than ten years after the Tremaglia law was introduced, the quality of the representation provided by MPs elected for the foreign constituency is often the subject of caricature, despite the MPs' many activities. The purpose of this article is to explore the kind of representation enjoyed by Italians resident abroad by looking, in particular, at the social and other characteristics of the members of Parliament representing the overseas constituency. The study, based on interviews and an analysis of legislative proposals, focuses on selection mechanisms and candidates' strategies with regard to political issues, the tools of communication they deploy and their links with their constituencies.